Nucleotídeos e ácido glutâmico em dietas de leitões desmamados - Santos, Luan Sousa dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objectives of this research were to evaluate the effects of nucleotides (NU) and glutamic acid (AG) in the diet of pigs on performance and plasma lipid profile (total cholesterol - CT, triglycerides - TRI, HDL cholesterol and LDL + VLDL cholesterol ) (experiment I) and turnover of 13C in duodenal and jejunum mucosa (13C half-life) (experiment II). In both experiments we used experimental design of randomized blocks, with 2x2 factorial treatments, with two levels of NU (0 and 0.1%) and two levels of AG (0 and 1%), each treatament had seven replicated and three pigs per pen. The first experiment lasted 35 days and were used 84 piglets weaned at 21 days of age and average initial weight of 6.54 ± 0,70kg. In the second experiment, on days 3, 6, 9, 14, 21, 34 and 49 after weaning, were slaughtered three pigs per treatment and the day of weaning (day zero) were slaughtered three piglets, totaling 87 animals with initial weight 6.28 ± 0,13kg. There was no interaction of factors in the analyzed variables and not effects of NU and AG in daily feed intake, daily weight gain, CT, HDL cholesterol, TRI, LDL + VLDL cholesterol and 13C turnover in the intestinal mucosa. The use of NU in the diet has worsened (p≤0.05) feed conversion in the period 0-27 days, but this variable was not affected in the total period (0-35 days). We observed a decrease (P<0.0001) in plasma concentration of all variables after 56 days compared to 21 days of age and in the jejunal mucosa the 13C half-life was higher in lighter piglets (p≤0.05). It can be concluded therefore that the addition of AG and NU in the diets did not affect performance, the plasma lipid profile and 13C turnover in the duodenum and jejunum mucosa of weaned piglets in total nursery period

Os objetivos desta pesquisa foram avaliar os efeitos da utilização de nucleotídeos (NU) e ácido glutâmico (AG) na dieta de leitões sobre o desempenho e perfil de lipídeos plasmáticos (colesterol total - CT, triglicérides - TRI, HDL colesterol e LDL+VLDL colesterol) (experimento I) e turnover do 13C na mucosa do duodeno e jejuno (meia-vida do 13C) (experimento II). Em ambos os experimentos foi utilizado delineamento experimental de blocos ao acaso, com esquema fatorial 2x2 dos tratamentos, sendo dois níveis de NU (0 e 0,1%) e dois níveis de AG (0 e 1%), com sete repetições e três animais por parcela. O primeiro experimento teve duração de 35 dias e foram utilizados 84 leitões desmamados aos 21 dias de idade e com peso médio inicial de 6,54±0,70kg. No segundo experimento, nos dias 3, 6, 9, 14, 21, 34 e 49 após o desmame, foram abatidos três leitões por tratamento e no dia do desmame (dia zero) foram abatidos três leitões, totalizando 87 animais com peso inicial de 6,28±0,13kg. Não houve interação dos fatores nas variáveis analisadas e nem efeitos de NU e do AG no consumo diário de ração, ganho diário de peso, CT, HDL colesterol, TRI, LDL + VLDL colesterol e no turnover do 13C na mucosa intestinal. O uso de NU na dieta piorou (P≤0,05) a conversão alimentar no período de 0 a 27 dias, mas esta variável não foi influenciada no período total de experimento (0 a 35 dias). Ocorreu redução (P<0,0001) na concentração plasmática de todas as variáveis estudadas aos 56 dias em relação aos 21 dias de idade e na mucosa do jejuno a meia-vida do 13C foi maior nos leitões mais leves (P≤0,05). Conclui-se, portanto, que a adição de NU e AG nas dietas não interferem no desempenho, no perfil lipídico plasmático e no turnover do 13C na mucosa do duodeno e jejuno de leitões recém-desmamados no período total de creche
Performance, plasma lipid profile and turnover of 13c in the intestinal mucosa of piglets fed with nucleotides and glutamic acid
Keywords: Nucleotídeos; Acido glutamico; Leitão (Suino) - Desmame precoce; Nucleotides